The Impact of Space Flight on Survival and Interaction of Cupriavidus metallidurans CH34 with Basalt, a Volcanic Moon Analog Rock - Byloos, Bo; Coninx, Ilse; Van Hoey, Olivier; Cockell, Charles; Nicholson, Natasha; Ilyin, Vyacheslav; Van Houdt, Rob; Boon, Nico; Leys, Natalie (Frontiers in Microbiology, 2017)
Microbe-mineral interactions have become of interest for space exploration as microorganisms could be used to biomine from extra-terrestrial material and extract elements useful as micronutrients in e.g. life support systems. This research aimed to identify the impact of space flight on the long-term survival of Cupriavidus metallidurans CH34 in mineral water and the interaction with basalt, a lunar-type rock in preparation for the ESA spaceflight experiment, BIOROCK. C. metallidurans CH34 cells were suspended in mineral water supplemented with or without crushed basalt and send for three months on board the Russian FOTON-M4 capsule. Afterwards, cell physiology analysis (by flow cytometry), cultivability analysis (by plate count), element analysis (by ICP-OES) and biofilm analysis (by scanning electron microscopy) were performed to study the effects of basalt and space conditions on C. metallidurans and element leaching and interaction with basalt. Space flight counteracted some of the detrimental effects seen during survival of C. metallidurans cells, after the three month storage at ambient conditions (18°C). Long-term storage had a significant impact on cell physiology and energy status as 60% of cells stored on ground lost their cell membrane potential, only 17% were still active, average ATP levels per cell were significantly lower and cultivability dropped to 1%. The cells stored in the presence of basalt and exposed to space flight conditions during storage however showed less dramatic changes in physiology, with only 16% of the cells lost their cell membrane potential and 24% were still active, leading to a higher cultivability (50%) and indicating a general positive effect of basalt and space flight on survival. Microbe-mineral interactions and biofilm formation was altered by spaceflight as less biofilm was formed on the basalt during flight conditions. Leaching from basalt also changed, showing that cells release more copper from basalt and the presence of cells also impacted iron and magnesium concentration irrespective of the presence of basalt.